Keanekaragaman Jenis Burung pada Berbagai Tipe Habitat di Pulau Belitung - Diandra Fauzia Lestari; Insan Kurnia (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
Belitung Island is a satellite island of the mainland of Sumatra Island. So far, bird research has been very rare and there have been almost no recent publications, so research on birds on Belitung Island is needed. The research was conducted during February-April 2020 in seven habitat types in 18 locations. Data were taken using the IPA (Index Point of Abundance) method with observation times between 05.30-09.00 am and 03.00-06.00 pm. Qualitative analysis was carried out on the bird status, while quantitative analysis was carried out using: 1) chi-square for bird species richness; 2) Shannon-Wiener diversity index (H'); 3) evenness index (E); and 4) bird community similarity index (IS). There were 111 bird species from 40 families and 13 orders. The birds found significantly different between habitat types for the number of species (χ²count = 23.73; df = 6; P < 0.05) and the number of individuals (χ²count = 361.65; df = 6; P < 0.05). The number of bird species found ranged from 14 species (lake habitat) to 50 bird species (coastal habitat). One bird species can be found in all habitat types, namely Cinnyris jugularis. Nine species of shorebirds were found. The bird diversity index (H') was obtained at 3.83 which is included in the high category and the bird evenness index (E) was obtained at 0.81 which is included in the high category and means the community is stable. The community similarity index (IS) values between habitat types ranged from 0.10-0.33.